2016
DOI: 10.3847/0004-637x/826/2/165
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRAINTS ON THE PRESENCE OF SiO GAS IN THE DEBRIS DISK OF HD 172555

Abstract: We have carried out two sets of observations to quantify the properties of SiO gas in the unusual HD 172555 debris disk: (1) a search for the J=8-7 rotational transition from the vibrational ground state, carried out with the Atacama Pathfinder EXperiment (APEX) submillimeter telescope and heterodyne receiver at 863 μmand (2) a search at 8.3 μm for the P(17) ro-vibrational transition of gas phase SiO, carried out with the Very Large Telescope (VLT)/VISIR with a resolution, λ/Δλ, of 30,000. The APEX measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…HD 172555 (HIP 92024, HR 7012) is one of the most studied objects among these special stellar systems (Cote 1987;Schütz et al 2005;Chen et al 2006;Wyatt et al 2007b;Lisse et al 2009;Smith et al 2012;Riviere-Marichalar et al 2012; Article number, page 1 of 16 arXiv:1808.04373v1 [astro-ph.EP] 13 Aug 2018 A&A proofs: manuscript no. HD172555_v7_arxiv Johnson et al 2012;Kiefer et al 2014;Wilson et al 2016;Grady et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HD 172555 (HIP 92024, HR 7012) is one of the most studied objects among these special stellar systems (Cote 1987;Schütz et al 2005;Chen et al 2006;Wyatt et al 2007b;Lisse et al 2009;Smith et al 2012;Riviere-Marichalar et al 2012; Article number, page 1 of 16 arXiv:1808.04373v1 [astro-ph.EP] 13 Aug 2018 A&A proofs: manuscript no. HD172555_v7_arxiv Johnson et al 2012;Kiefer et al 2014;Wilson et al 2016;Grady et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from this, several stars with hot disks have been found (Wyatt et al 2007a;Fujiwara et al 2009) based on the IR excess with an estimate temperature above 300 K. The stars that possess hot dust are very interesting targets because the submicron-sized grains at a small small distance from a star could be a signpost for transient collision events. HD 172555 (HIP 92024, HR 7012) is one of the most studied objects among these special stellar systems (Cote 1987;Schütz et al 2005;Chen et al 2006;Wyatt et al 2007b;Lisse et al 2009;Smith et al 2012;Riviere-Marichalar et al 2012;Johnson et al 2012;Kiefer et al 2014;Wilson et al 2016;Grady et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A strong signature of 'SiO gas' is also present. However, since Lisse 2009, studies by Johnson et al 2012 andWilson et al 2016 cast some doubt on the presence of this species, both from a photolytic stability and an actual measurement standpoint. The amorphous silicates/silica study of Speck et al 2011, and the Mars Spirit rover study of Ruff et al 2011 have demonstrated that this 8 µm shoulder feature may be a solid state feature found in hydrated forms of silica like hyalite (but not unhydrated forms like obsidian, cristobolite, or tektite).…”
Section: Mineralogical Modeling Resultsmentioning
confidence: 99%
“…Lisse et al (2009) suggested the presence of silica emission in mid-IR spectra of HD 172555, as the parent molecule for atomic oxygen. This interpretation has subsequently been questioned (Wilson et al 2016). If vaporized and photodissociated, SiO dissociation should produce silicon and oxygen ion profiles that closely resemble each other.…”
Section: Discussionmentioning
confidence: 99%